2021
DOI: 10.4085/351-20
|View full text |Cite
|
Sign up to set email alerts
|

Explosive Quadriceps Strength Symmetry and Landing Mechanics Limb Symmetry After Anterior Cruciate Ligament Reconstruction in Females

Abstract: Context Emerging evidence suggests that lower quadriceps rate of torque development (RTD) following anterior cruciate ligament reconstruction (ACLR) may be associated with altered landing mechanics. However, the influence of quadriceps RTD magnitude and RTD limb symmetry on landing mechanics limb symmetry remains unknown. Objective To assess the influence of quadriceps RTD magnitude and RTD limb symmetry on sagittal plane lan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…During jumping tasks, RTD LSI accounted for only 21% of the variance in knee extensor moment symmetry at initial contact during the landing phase of a double-leg drop jump, but was not a significant predictor during the single-leg drop jump in a cross-sectional study (mean, 20.1 6 9.1 months after ACLR; only female athletes). 19 Specific to running, a crosssectional study at a mean of 48.0 6 25.0 months after ACLR athletes demonstrated a low correlation between isokinetic PT and rate of knee extensor moment (r = 0.38) and between RTD (0-100 ms from onset) and rate of knee extensor moment (r = 0.26). 35 A prospective study that assessed the relationships between quadriceps RTD and hop performance at 3 and 6 months after ACLR found a similar variance explained (R 2 ~0.4) when both RTD and PT were included in the model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…During jumping tasks, RTD LSI accounted for only 21% of the variance in knee extensor moment symmetry at initial contact during the landing phase of a double-leg drop jump, but was not a significant predictor during the single-leg drop jump in a cross-sectional study (mean, 20.1 6 9.1 months after ACLR; only female athletes). 19 Specific to running, a crosssectional study at a mean of 48.0 6 25.0 months after ACLR athletes demonstrated a low correlation between isokinetic PT and rate of knee extensor moment (r = 0.38) and between RTD (0-100 ms from onset) and rate of knee extensor moment (r = 0.26). 35 A prospective study that assessed the relationships between quadriceps RTD and hop performance at 3 and 6 months after ACLR found a similar variance explained (R 2 ~0.4) when both RTD and PT were included in the model.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with previous studies, we detected stronger associations between RTD and movement mechanics in individuals after ACLR. 19,26,35 Possible explanations for this discrepancy include variations in the methods used to calculate RTD (eg, RTD 20%-80% vs 0-100 ms from onset), time frames assessed postoperatively, the task performed (eg, running vs single-leg hop for distance), and/or the biomechanical variables of interest. During jumping tasks, RTD LSI accounted for only 21% of the variance in knee extensor moment symmetry at initial contact during the landing phase of a double-leg drop jump, but was not a significant predictor during the single-leg drop jump in a cross-sectional study (mean, 20.1 ± 9.1 months after ACLR; only female athletes).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Out of the four parameters identified (eccentric deceleration impulse, concentric impulse, landing impulse and jump height) only the eccentric deceleration impulse significantly decreased between 6 and 9 months post-ACLR [13]. [32,39,51,55], with one study not reporting participants' sex [37]. Amongst the five studies, eleven unique parameters were identified.…”
Section: Double-leg Cmjmentioning
confidence: 99%
“…No other kinetic parameters were reported [33]. [8,9,17,19,22,31,32,41,42,46,48,53,61,63,64]. Two studies did not report the participants' sex [19,41].…”
Section: Single-leg Djmentioning
confidence: 99%